Tyre Volume and Pressure Effects on Impact Attenuation during Mountain Bike Riding - Paul W. Macdermid; Matthew C. Miller; Fiona M. Macdermid; Philip W. Fink (Shock and Vibration)
Exposure to impacts and vibrations has been shown to be detrimental to cross country mountain bike performance and health. Therefore, any strategy aimed at attenuating such exposure is useful to participants and/or industry. The purpose of this study was to assess the influence of tyre size and tyre inflation pressure on exposure to impacts. Participants completed nine trials of a technical section (controlled for initial speed and route taken) including nine separate conditions involving three tyre sizes and three tyre inflation pressures normalised per tyre. Performance was determined by time to negotiate the technical section while triaxial accelerometers recorded accelerations (128 Hz) to quantify impact exposure and the subsequent effects on soft tissue response. Increases in tyre size within the range used improved performance P<0.0001 while changes to tyre inflation pressure had no effect P=0.6870 on performance. Larger tyre sizes and lower tyre inflation pressures significantly P<0.0001 reduced exposure to impacts which could be augmented or negated due to an interaction between tyre size and inflation pressure P<0.0001. It is recommended that mountain bikers use larger tyres, inflated to the moderate pressures used within this study, in order to increase performance and reduce the risk of overuse injuries.